Comparison of hydrogel pad and water-circulating blanket cooling methods for targeted temperature management: A propensity score-matched analysis from a prospective multicentre registry. (December 2021) - Keum, Kyoung Tak; Kim, Yong Hwan; Lee, Jun Ho; Ahn, Seong Jun; Hwang, Seong Youn; Oh, Joo Suk; Kim, Su Jin; Kim, Soo Hyun; Jeung, Kyung Woon; ,
Abstract: Background: Various methods have been used to control body temperature in targeted temperature management (TTM), but few studies have compared specific subtypes of surface cooling systems. The aim of this study was to compare the efficiencies and neurological outcomes between hydrogels pad and water-circulating blanket cooling methods. Methods: We conducted a multicentre, prospective, registry-based study of out-of-hospital cardiac arrest patients treated with TTM between 2015 and 2018. We compared the neurological outcomes, efficacies for cooling, and adverse events between patients who received TTM using a hydrogel pad and water-circulating blanket cooling. Patients were one-to-one matched using propensity scores to adjust for differences in the baseline characteristics of each cooling method. The primary outcome was a favourable neurological outcome at 6 months. Results: We included 1, 132 patients in the analysis, 870 of whom underwent hydrogel pad cooling, and the remaining 262 underwent water-circulating blanket cooling. In the unmatched cohort, a greater number of adverse events occurred in the water-circulating blanket group. The favourable neurologic outcome rates at 6 months were similar between the hydrogel pad group and the water circulating blanket group (30.2% vs. 29.8%, p = 0.939). In the propensity-matched cohort, which included 184 pairs, the rates of adverse events between the two groups were similar. The similarity of favourable neurologic outcome rates at 6 months between the two groups persisted (28.8% vs. 29.9%, p = 0.819). Conclusion: Neurological outcomes and adverse events between the hydrogel pad cooling and water-circulating blanket cooling groups were similar.